Assessing Ticket.com App Usability Through the System Usability Scale (SUS) Method - Putri, Shiffa Intania; Liu, Kevin (Bright Institute, 2024)
The influence of technology has increased ease and comfort, especially in the online ticket ordering process. One of the online ticket booking platforms that is popular among users is Tiket.com. However, on the Tiket.com application, there are still various negative reviews given by users. One way to maintain an application is to pay attention to usability aspects, especially user input. So, this research aims to evaluate the Tiket.com application in terms of usability using the System Usability Scale (SUS) method as a data processing method. The results obtained from calculating the SUS score in usability evaluation were 55.55. This score shows that the usability level of the Tiket.com application is quite good, with the Adjective Ranking being in the OK category, and Acceptable at Marginal level and Grade D level. Even though the assessment results are acceptable, there are various things that need to be considered, including increasing the use of features. to function properly and pay attention to every user input. This is done so that it can have a significant impact on the Tiket.com application, especially in improving the usability aspect.